1989
DOI: 10.2118/15969-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Quadratic Gradient Term in Steady-State and Semisteady-State Solutions for Reservoir Pressure

Abstract: Summary Constant-rate analytical solutions of the one-phase radial-flow equation in two dimensions, including effects of the quadratic gradient term, are derived for an oil reservoir with constant diffusivity and compressibility. The combinations of compressibility contributions to the various terms are analyzed. It is shown that the standard condition allowing the quadratic gradient term to be neglected (cp less than 1) is incorrect; pressure, p, should be replaced by a function of the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The notation ch represents the bulk volume compressibility for a reservoir which can expand or contract in a vertical direction perpendicular to flow for D = 1 and D = 2 (for D = 3, in our approach, Ch = 0). With r and t being the radial (linear) and time variables, Finjord and Aadnoy (1989) have shown that the Darcy continuity equation (Dake, 1978) has the form {~p~2 1 a (ap) In what follows, we will treat the diffusivity as a constant and also assume that el > 0. We therefore specialize to the limit where CO and ch are much more dominant than the other compressibilities.…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notation ch represents the bulk volume compressibility for a reservoir which can expand or contract in a vertical direction perpendicular to flow for D = 1 and D = 2 (for D = 3, in our approach, Ch = 0). With r and t being the radial (linear) and time variables, Finjord and Aadnoy (1989) have shown that the Darcy continuity equation (Dake, 1978) has the form {~p~2 1 a (ap) In what follows, we will treat the diffusivity as a constant and also assume that el > 0. We therefore specialize to the limit where CO and ch are much more dominant than the other compressibilities.…”
Section: Assumptionsmentioning
confidence: 99%
“…Usually, the latter term has been neglected when analytical solutions have been sought. Exact analytical solutions, including the quadratic gradient-term effects, have been found by Finjord and Aadnoy (1989) for steady-state and semisteady-state flow for the case where the variability of the diffusivity can be neglected. This is allowed for particular parameter values and also in the limit of small nonlinear effects where a first-order perturbative approach is allowed.…”
Section: Introductionmentioning
confidence: 99%
“…3 with the assumption of pressure-dependent rock properties, we obtain 02p +~ op +~ ok (Op)2 + kp CL(Op)2 = c/>p. (cL +c ma ) oP, ~~ (rk :)= 2:h' ............................. (8). 3 with the assumption of pressure-dependent rock properties, we obtain 02p +~ op +~ ok (Op)2 + kp CL(Op)2 = c/>p. (cL +c ma ) oP, ~~ (rk :)= 2:h' ............................. (8).…”
mentioning
confidence: 93%
“…For conventional Darcy's flow models, using a Laplace transform, Odeh and Badu [52] presented analytical solutions to nonlinear partial differential equations (PDEs) taking into consideration the quadratic pressure gradient term, describing the seepage flow of a slightly compressible fluid; it was concluded that the nonlinear solutions showed the pressure difference for injection and pumping conditions, in comparison with the generally accepted solutions of linearized equations. Finjord et al [53] obtained constant-rate analytical solutions of a one-phase radial flow equation, considering the effect of the quadratic pressure gradient term, in an oil reservoir with constant diffusivity and compressibility. Wang and Dusseault [54] developed an analytical solution for pore pressure coupled with deformation in porous media; the quadratic pressure gradient term was taken into account, and it was shown that existing solutions deviated when the pressure gradient was high.…”
Section: Introductionmentioning
confidence: 99%